Optimation of Transportation Cost Distribution in PT Saprotan Utama Nusantara Uses Transportation Models - Nugrahadi, Bekti; Sadewa, Rifky Ian; Primasanti, Yunita; Indriastiningsih, Erna (ARRUS Journal of Engineering and Technology, 2024)
PT Saprotan Utama Nusantara is a company that operates in the field of agricultural products, one of which is herbicide fertilizer. The distribution costs for herbicide products incurred by the company in 2020 to 2023 have quite a large value, in 2020 amounting to Rp 148.523.000, in 2021 amounting to Rp 157.500.000, in 2022 amounting to Rp 145.800.000 and in 2023 amounting to Rp 147.900.000. These costs are not optimal and fluctuate so they have an impact on company profits. The aim of this research is to produce optimal distribution cost values using a transportation model. Then data processing was carried out using a transportation model with the North West Corner, Least Cost, Vogel Approximation, Stepping Stone and POM QM software methods. In the distribution of herbicide fertilizer from January to December 2023, data processing was carried out at PT Saprotan Utama Nusantara as a comparison between actual costs and optimal costs using a transportation model. The company's total costs during the year reached Rp 147.900.000, but after implementing the transportation model, the optimal costs were Rp 124.650.000. This shows a cost savings of Rp 23.250.000.